Evaluasi Proses Penelusuran Literatur dan Penerapan Topik-Tema dalam Perancangan Arsitektur - Nurdiani, Nina (Bina Nusantara University, 2012)
Topics and themes become the key to open the insights of both theoretical and practical knowledge in architectural design; a concept in architectural design related issue as well. Ideally, the students of architecture do researches to generate new design ideas or proper design solutions. Prior to doing researches, it is necessary for them to find out how far the process of searches – literature review and application of topics and themes in the architectural design – have been done. This study was conducted with descriptive approach through case studies. The analysis unit is the final students of design studio class and students of the final project in the Department of Architecture, Faculty of Engineering, Binus University - Jakarta. The Results of the study illustrate that the architecture students of Binus University know and learn about the architecture research. However, they need the efforts to improve research skills, accurate literature searches, as well as exercise and evaluation of the implementation of topic-themes that started to be studied by students from the mid-level to theadvance-level. The results of this study will be inputs to support architectural design learning based on architectural research at the Department of Architecture, especially in Binus University.